Willingness to Pay for Air Quality Improvements in Sofia, Bulgaria - Wang, Hua; Whittington, Dale (World Bank, Washington, DC, 2015)
Through a survey the authors study willingness to pay for improvements in air quality in Sofia, Bulgaria. Using a stochastic payment car approach - asking respondents the likelihood that they would agree to pay a series of prices - they estimate the distribution of willingness to pay various prices. They find that people in Sofia are willing to pay up to about 4.2 percent of their income for a program to improve air quality. The income elasticity of willingness to pay for air quality improvements is about 27 percent. For comparison, they also used the referendum contingent valuation approach. Results from that approach yielded a higher estimate of willingness to pay.